2011
DOI: 10.1242/dev.074591
|View full text |Cite
|
Sign up to set email alerts
|

The role of Pax6 in regulating the orientation and mode of cell division of progenitors in the mouse cerebral cortex

Abstract: SUMMARYSuccessful brain development requires tight regulation of sequential symmetric and asymmetric cell division. Although Pax6 is known to exert multiple roles in the developing nervous system, its role in the regulation of cell division is unknown. Here, we demonstrate profound alterations in the orientation and mode of cell division in the cerebral cortex of mice deficient in Pax6 function (Pax6 Sey/Sey ) or after acute induced deletion of Pax6. Live imaging revealed an increase in non-vertical cellular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 91 publications
3
76
0
Order By: Relevance
“…However, the Sey/Sey (Pax6 mutant) mouse cortex shows an increased occurrence of abventricular centrosomes that is paralleled with an increase in subapical and basal mitosis (Asami et al 2011, Tamai et al 2007). Indeed, Pax6 directly regulates ciliary and centrosomal components, such as Spag5 (Asami et al 2011), suggesting a possible link between centrosome/cilium localization and fate transition.…”
Section: Cilium Localization and Fate Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Sey/Sey (Pax6 mutant) mouse cortex shows an increased occurrence of abventricular centrosomes that is paralleled with an increase in subapical and basal mitosis (Asami et al 2011, Tamai et al 2007). Indeed, Pax6 directly regulates ciliary and centrosomal components, such as Spag5 (Asami et al 2011), suggesting a possible link between centrosome/cilium localization and fate transition.…”
Section: Cilium Localization and Fate Transitionmentioning
confidence: 99%
“…However, the Sey/Sey (Pax6 mutant) mouse cortex shows an increased occurrence of abventricular centrosomes that is paralleled with an increase in subapical and basal mitosis (Asami et al 2011, Tamai et al 2007). Indeed, Pax6 directly regulates ciliary and centrosomal components, such as Spag5 (Asami et al 2011), suggesting a possible link between centrosome/cilium localization and fate transition. Consistent with this observation, it has been demonstrated recently that in cells undergoing delamination (e.g., newborn basal progenitors and neurons), the cilium is localized basolaterally rather than apically (Wilsch-Bräuninger et al 2012).…”
Section: Cilium Localization and Fate Transitionmentioning
confidence: 99%
“…In the cerebral cortex of the mouse embryo aRGCs and bRGCs express the paired‐box transcription factor Pax6 and not the T‐box transcription factor Tbr2, whereas IPCs express Tbr2 but not Pax6 (a small percentage of mouse bRGCs have been reported to express Tbr2 by some authors, so this point remains controversial; Shitamukai et al, 2011; Wang et al, 2011). Whereas Pax6 has a critical role in the definition of telencephalic territories and multiple aspects of cortical progenitor proliferation (Asami et al, 2011; Estivill‐Torrus et al, 2002; Gotz et al, 1998; Kroll and O'Leary, 2005; Mi et al, 2013; O'Leary and Sahara, 2008; Schuurmans and Guillemot, 2002; Sur and Rubenstein, 2005), Tbr2 has an instructive role in defining the conversion of aRGCs into IPCs (Sessa et al, 2008). In agreement with these roles, Pax6 and Tbr2 expression follows a unidirectional sequence in the cortical progenitor lineage: first Pax6 (aRGCs, bRGCs), second Tbr2 (some bRGCs, IPCs and newborn neurons; Englund et al, 2005; Hevner, 2006).…”
Section: Molecular Regulation: Evo‐devo Lessons From Transcriptomicsmentioning
confidence: 99%
“…The expression of ZO-1-or Par3-EGFP fusion proteins (which localize to the zonula adherens) marks the cell-cell boundary at the apical junctional level (Konno et al 2008;Shitamukai et al 2011). Imaging these fluorescent markers from the apical side of brain slices allows the direct observation of the partitioning of the apical junction into daughter cells and has revealed that the segregation of the apical membrane exclusively to a single daughter cell occurs in only 10%-20% of RG divisions during the neurogenic stage of the developing murine brain (Konno et al 2008;Asami et al 2011;Shitamukai et al 2011); indeed the apical junction is partitioned between both daughter cells in the majority of RG cell divisions. The reextension of the lost apical end is rarely observed in divisions during the midneurogenic stage (E14-E16).…”
Section: Asymmetric Segregation Of Epithelial Substructures During Rgmentioning
confidence: 99%